Political and Governance Challenges to Achieving Global HIV Goals with Injecting Drug Users: The Case of Pakistan - Hina Khalid; Ashley M. Fox (Kerman University of Medical Sciences, 2019)
Background The Joint United Nations Programme on HIV/AIDS (UNAIDS) has recently set the ambitious "90-90-90 target" of having 90% of people living with HIV (PLHIV) know their status, receive antiretroviral therapy (ART), and achieve viral suppression by 2020. This ambitious new goal is occurring in a context of global "scale-down" following nearly a decade of heightened investment in HIV prevention and treatment efforts. Arguably international goals spur action, however, setting unrealistic goals that do not take weak health systems and variations in the nature of the epidemic across countries into consideration may set them up for failure in unproductive ways that lead to a decline in confidence in global governance institutions. This study explores how policy actors tasked with implementing HIV programs navigate the competing demands placed upon them by development targets and national politics, particularly in the current context of waning international investments towards HIV.   Methods To examine these questions, we interviewed 29 key informants comprising health experts in donor organizations and government employees in HIV programs in Pakistan, a country where HIV programs must compete with other issues for attention. Themes were identified inductively through an iterative process and findings were triangulated with various data sources and existing literature.   Results We found both political and governance challenges to achieving the target, particularly in the context of the global HIV scale-down. Political challenges included, low and heterogeneous political commitment for HIV and a conservative legal environment that contributed towards a ban on opiate substitution therapy, creating low treatment coverage. Governance challenges includedstrained state and non-governmental organization (NGO) relations creating a hostile service delivery environment, weak bureaucratic and civil society capacity contributing to poor regulation of the health infrastructure, and resource mismanagement on both the part of the government and NGOs.   Conclusion Our findings suggest that in a context of waning international attention to HIV, policy actors on the ground face a number of practical hurdles to achieving the ambitious targets set out by international agencies. Greater attention to the political and governance challenges of implementing HIV programs in low- and middle-income countries (LMICs) could help technical assistance agencies to develop more realistic implementation plans.